Efficacy of Artocarpus heterophyllus leaf extract mouthwash in gingivitis subjects: a clinico microbiological study - Kalburgi, Nagaraj B.; Koregol, Arati C.; Nikhil, Bilakanti; Roy, Anjaly; Sulthana, Uzma Parveen; Hiremath, Jayadev N. (International Journal Of Community Medicine And Public Health, 2025)
Background: Gingivitis is the inflammatory disease of gingiva that supports the teeth. The prevailing belief regarding the cause of gingivitis is the toxins produced by anaerobic bacteria in oral cavity particularly that cause the formation of plaque. The tropical climacteric fruit Artocarpus heterophyllus, commonly known as jackfruit possess anti carcinogenic, antimicrobial, antifungal, anti-inflammatory, wound-healing and hypoglycaemic properties. Hence the objective of this study is to evaluate clinical parameters at baseline and 21 days post non-surgical periodontal therapy after the use of jackfruit leaf extract mouthwash and to evaluate the colony count of P. gingivalis in plaque samples at baseline and 21 days after the use of jackfruit leaf extract mouthwash. Methods: A total of 30 gingivitis subjects were selected and divided randomly into group A and B. Group 1, non-surgical periodontal therapy alone (15). Group 2, non-surgical periodontal therapy followed by jackfruit leaf extract mouthwash (15). The supra gingival plaque samples were collected from both the groups at baseline and 21 days post non-surgical periodontal therapy. Results: Significant reduction in clinical parameters and colony count of P. gingivalis after the use of Artocarpus heterophyllus mouthwash. Conclusions: Jackfruit leaf extract mouthwash has better promising effect on inflammation in gingivitis subjects when compared to gingivitis subjects with non-surgical periodontal therapy alone.